The relationship between ferroptosis and respiratory infectious diseases: a novel landscape for therapeutic approach - Hong, Longyan; Chen, Xiangyu; Liu, Yiming; Liang, Hao; Zhao, Yinghui; Guo, Pengbo (Frontiers in Immunology, 2025)
Respiratory infectious diseases, particularly those caused by respiratory viruses, have the potential to lead to global pandemics, thereby posing significant threats to public and human health. Historically, the primary treatment for respiratory bacterial infections has been antibiotic therapy, while severe cases of respiratory viral infections have predominantly been managed by controlling inflammatory cytokine storms. Ferroptosis is a novel form of programmed cell death that is distinct from apoptosis and autophagy. In recent years, Recent studies have demonstrated that ferroptosis plays a significant regulatory role in various respiratory infectious diseases, indicating that targeting ferroptosis may represent a novel approach for the treatment of these conditions. This article summarized the toxic mechanisms underlying ferroptosis, its relationship with respiratory infectious diseases, the mechanisms of action, and current treatment strategies. Particular attentions were given to the interplay between ferroptosis and Mycobacterium tuberculosis, Epstein-Barr virus, severe acute respiratory syndrome coronavirus-2, Pseudomonas aeruginosa, dengue virus, influenza virus and herpes simplex virus type1infection. A deeper understanding of the regulatory mechanisms of ferroptosis in respiratory infections will not only advance our knowledge of infection-related pathophysiology but also provide a theoretical foundation for the development of novel therapeutic strategies. Targeting ferroptosis pathways represents a promising therapeutic approach for respiratory infections, with significant clinical and translational implications.